The Importance of Sociolinguistics in Foreign Language Education: A Review of Selected Paper - Nasution, Jimmy Saputra; Rahmadeny, Muhammad; Jazzawi, Ichsan (International Journal for Educational and Vocational Studies, 2019)
This article aims to provide a brief description and review of the research conducted by Yasemin Bayyurt entitled "Current Perspectives on Sociolinguistics and English Language Education" published in The Journal of Language Teaching and Learning, using descriptive qualitative analysis, and this paper tries to understand the importance of sociolinguistics in learning foreign languages from the perspective of the researcher. In this paper, the position and importance of sociolinguistics in foreign language education is the main topic in this article. This article is intended to provide a brief review of sociolinguistics and its importance in learning foreign languages. The findings in this study see that the research of Yasemin Bayyurt discusses and develops the definition of linguistic language and the relationship between sociolinguistics and foreign language education which will be explored in depth in 4 focuses. In it also mentioned the existence of several basic problems discussed in the sociolinguistic field, one example of which is variation and change language. The author examines this in three dimensions, namely the attitude towards foreign language learning, the inclusion of culture in foreign language learning, and the contribution of language planning to foreign language education. So with the findings in this study, hopefully it can be a reference for readers and hope that it can also be a replica in real life.